Molecular-size dependence of glycogen enzymatic degradation and its importance for diabetes. (September 2016) - Jiang, Xiaoyin; Zhang, Peng; Li, Shihan; Tan, Xinle; Hu, Zhenxia; Deng, Bin; Wang, Kai; Li, Cheng; Sullivan, Mitchell A.; Li, Enpeng; Gilbert, Robert G.
Graphical abstract: Highlights: Glycogen, a complex branched glucose polymer, helps maintain blood-sugar level. Small β particles bind into large α particles; the binding is fragile in diabetes. We study the time evolution of molecular size distribution with degradative enzyme. This shows small particles degrade more rapidly to glucose than large ones. This is consistent with uncontrolled blood sugar levels in diabetes. Abstract: Glycogen, a hyperbranched glucose polymer, is the blood-sugar reservoir in animals. Liver glycogen comprises small β particles, which can join together as large composite α particles. It had been shown that the binding between β in α particles in the liver of diabetic mice is more fragile than in healthy mice. This could be linked to the loss of blood-sugar control characteristic of diabetes if the rate per monomer unit of the enzymatic degradation to glucose of α particles were significantly slower than that of β particles. This is tested here by examining the in vitro time evolution of the molecular size distribution of glycogen from the livers of healthy and diabetic mice and rats, containing distinct components of both α and β particles; this treatment is analogous to the "competitive growth" method used to explore mechanisms in emulsion polymerization. Simulations for the time evolution of the molecular size distribution were also performed. It is found that the degradation rate per monomer unit is indeed faster for the smaller particles, supporting the hypothesis of a causal link between chemical fragility of glycogen from diabetic liver with poor control of blood-sugar release. Comparison between simulations and experiment indicate that α and β particles have significant structural differences.